Exploring the Regional Instruments of Iranian Folk Music (Música Hodie, 2026)
Iranian folk music, one of the oldest and richest cultural heritages, plays a crucial role in shaping the cultural identity of this nation. This article examines the structure, technical characteristics, and historical aspects of Iranian folk musical instruments. The interdisciplinary study–combining historical research, anthropology, and musical analysis–aims to deepen the understanding of these instruments and their role in regional music. This study was collected through extensive field research, interviews with folk music masters, and reviews of written and oral sources. This article builds on the author's previous research, " The Iranian National Musical Instruments and Their Techniques" (Link: revistas.ufg.br/musica/article/view/80795), which explored Iranian national musical instruments in greater detail. In this section, the main focus is on regional and folk instruments of Iran, including their structural features, playing techniques, and their social and cultural roles within folk communities. The findings indicate that Iranian folk instruments, beyond their structural diversity, play a significant role in religious ceremonies, social events, and daily life. Additionally, by analyzing playing techniques and cultural influences, this study explores the challenges of preserving and revitalizing these instruments while proposing strategies to sustain this valuable heritage. The novelty of this research lies in its comprehensive analysis of the technical, historical, and cultural dimensions of Iran's folk instruments and its effort to safeguard and revive them.